Transformation of Companies and Trade in the Era of Society 5.0 - Sisca Ferawati Burhanuddin; Gandhi Pharmacista (International Journal of Science and Society, 2023)
Rapid technological disruption is causing unprecedented changes in every aspect of human life. The entry into the new era of society 5.0, defined as the convergence between the physical world and the digital world, and seeks to place humans at the center of innovation. Society 5.0 tries to balance economic progress with solving social problems using a more strategic and dynamic system. This research uses a descriptive analysis method with a qualitative approach, while the use of qualitative is based on its very relevant function, especially in evaluating and understanding the condition of a group of people, the results of this research explain that, society 5.0 is a time where technology and humans will always coexist to improve quality. sustainable standard of living. The era of society 5.0 is human-centered, and digital technology is part of humans themselves. In the digital era, advances in digital technology are applied on various platforms, for example in the world of business and business there is ease of trade transactions, because the process is available anytime and anywhere, the era of digital transformation has changed the way many businesses operate, communicate and compete, so through this era Society 5.0 is expected to allow humans and information technology to work hand in hand and contribute to achieving sustainable development goals.